“GERAHAM MODEL” As a Strategy to Improve Mother’s Behaviour Maintance in Brushing Teeth - Rasipin Rasipin; Masrifan Djamil; Bedjo Santoso (Jurnal Kesehatan Gigi, 2022)
The results of Riskesdas 2018, showed 93% of children aged 5-6 years had dental caries with an average DMF-T of 8.3; as many as 57.6% experienced dental and oral health problems, and only 10.2% received services from medical personnel. The number of dental health problems in Central Java is below the national threshold of 57.6%. The proportion of dental health problems in Indonesia is still far from the expectation of achieving the long-term target of the Ministry of Health in 2030. Indonesia is caries-free. The aims of this study was to produce a "GERAHAM Model" to improve the behavior of mothers in brushing their teeth Research and Development (RD) methods, there are two stages of research, model development and testing the effect of the model using the quasi experiment method with one group pretest and posttest design. The GERAHAM model is a model that involves the mother's role in training children's habits to maintain oral hygiene, especially brushing teeth at home. The data were tested using the Wilcoxon test. The average results of knowledge before and after treatment were 10.20 and 12.70, while attitudes were 18.34 and 29.32, actions were 3.00 and 18.34. The Wilcoxon test showed that the molar model could increase the mother's knowledge, attitudes and actions (P=0.000). Conclusion: GERAHAM teeth model is relevant as a model of dental health education to shape maternal behavior in brushing teeth.